Improving DFT-based approaches to study CO2 electroreduction on transition metals (2021)
The industrial-scale conversion of electricity obtained from renewable sources is crucial to achieve an economy based on renewable energy. In that scenario, the electrochemical reduction of CO2, offers the possibility of producing some of the most demanded fuels and chemicals in a sustainable way. However, its efficient implementation on industrial scale is limited by factors as the high energy requirements for the product formation, the low selectivity and efficiency of electrolyzers, and the long-term deactivation of the catalysts. Understanding the many aspects that influence the reaction behavior is a challenging task because, apart from solvent and electrolyte effects, there are multiple intermediates, pathways, and products possible under similar operating conditions. In the recent decades this research field has been highly active in theory and experiments, and many studies have focused on finding the main factors that enhance the reaction performance. In this thesis, the electrochemical CO2 reduction is studied using state-of-the-art density functional theory (DFT) simulations, incorporating solvation effects as a crucial factor for improving thermodynamic predictions. To this end, a systematic micro-solvation method was developed to determine the number of hydrogen-bonded water molecules in the first solvation shell and the energetic stabilization granted by those hydrogen bonds. The reduction of CO2 to CO, CH4 and CH3OH on Cu, was considered to test this method, finding very good agreement with experiments without the need to include calculations of reaction kinetics. The estimation of solvation contributions for the CO2 reduction to CO has been extended to other transition metals such as Ag, Au, and Zn, finding significant variations between solvation corrections for the same adsorbates on different metals and finding very good agreement with experimental results. The increase in accuracy of the predictions make possible the development of a semiempirical method to explain the deactivation evidenced experimentally on Cu electrodes during CO2RR to CH4.